In vitro investigation of the effect of anti-inflammatory and analgesic drugs on measurement of tumor markers - Taşkıran, Hüseyin; Gönel, Ataman (Bentham Science Publishers, 2022)
Background: It has been shown that some drugs used as parenteral affect biochemical measurements. Anti-inflammatory and analgesic drugs may also have the potential to affect measurement methods. Objective: The aim of the study was to investigate the effects of seven different anti-inflammatory and analgesic pharmacological agents commonly used in wards and intensive care units on thy-roglobulin, CA125, CA15-3, CA19-9, CEA, PSA and total HCG tests measured by immunoassay technique. Methods: The study was performed using hormone control material (BioRad Lyphocheck Immunoassay Plus Control) in the PETINIA immunoassay method (Siemens, Atellica, USA). 20 µL of tenoxicam, dexamethasone, methylprednisolone, paracetamol, diclofenac sodium, dexketoprofen, and metamizole sodium were added into 180 µL of the control solution, respectively. After vortex-ing the sample, it was incubated for 20 minutes at room temperature. Thyroglobulin, CA125, CA15-3, CA19-9, CEA, total PSA and total HCG tests were studied from the control sample. The study was re-performed by adding 20 µL of distilled water. The measurements were repeated 3 times, and the mean values were recorded. Percentage deviation rates from the target value were calculated. Results: Metamizole sodium led to negative interference in the CA 19-9, total HCG, CA 125, CEA, total PSA and CA15-3 at a rate of-42.1%,-24.62%,-24.34%,-23.66%,-14.33%, and-13.91%, respectively. With the administration of metamizole sodium, the only positive interference was determined at a rate of 6.02% in thyroglobulin. Paracetamol-induced maximum deviation was calculated at the rate of-26.41% in CA 19-9. CA 19-9 deviated-12.22% from diclofenac sodium and-22.41% from dexketoprofen. With methylprednisolone administration, positive interference was detected at a rate of 14.46% in thyroglobulin and negative interference at a rate of-12% in total PSA. The highest deviation due to dexketoprofen was seen in CA 19-9 at a rate of-22.41%. Conclusion: This study demonstrated the potential of anti-inflammatory, analgesic, and antipyretic agents to affect tumor marker measurements. Especially in the follow-up of cancer patients, anti-inflammatory interference may increase the likelihood of malpractice by causing erroneous clinical evaluations. © 2022 Bentham Science Publishers.
Keywords: analgesics; anti-inflammatory drugs; false result; total PSA